Charting a Way Ahead : The Results Agenda - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, makes the case for ending poverty in our lifetime, especially in Africa. There is an urgent need for action, because thousands of people living in extreme poverty, many of them children, die every day from preventable diseases. The call to end poverty reaches across generations, continents, and nationalities. It spans religions, gender, and politics. Wolfowitz claims that the world is at a turning point, with grounds for hope. The last few decades have witnessed dramatic improvement in the condition of the world's poorest people. He cites as key factors leadership and accountability, respect for women, civil society, the private sector, and legal empowerment of the poor. He concludes that in order to find solutions for alleviating poverty, the World Bank needs to strengthen its knowledge and expertise in such areas as education, health, infrastructure, energy and sustainable development, and agriculture. We must chart a course for a future in which today's poor become tomorrow's entrepreneurs.